Techno-economic feasibility assessment of CO2 capture from coal-fired power plants using molecularly imprinted polymer - Hanak, Dawid P.; Manovic, Vasilije (Elsevier, 2017)
Mature CO2 capture technologies would reduce the net thermal efficiency of the coal-fired power plant by 7–13% points, leading to an electricity cost increase of at least 60%. To minimise the energy-intensity of CO2 capture, novel technologies and CO2 capture materials are being developed. This study assessed the techno-economic feasibility of the CO2 capture system using acrylamide-based molecularly imprinted polymer (MIP) sorbent in a 580 MWel coal-fired power plant retrofit scenario. Under the initial design basis, the net efficiency penalty and the energy penalty of the MIP retrofit scenario were estimated to be 5.3%HHV points and 14.1%, respectively. Furthermore, the cost of CO2 avoided was estimated to be 29.3 £/tCO2. Such techno-economic performance was found to be superior to the CO2 capture system using chemical solvents. The parametric study revealed that the thermodynamic performance of the MIP retrofit scenario is mainly affected by the sorbent capacity, as the net efficiency penalty was found to increase from 4.4 to 8.9%HHV points on reduction of the sorbent capacity from 1 to 0.2 mmol CO2/g. Moreover, the economic performance was not only found to be affected by sorbent capacity, but primarily on the cyclic performance of the MIP sorbent. It was shown that the cost of CO2 avoided would increase linearly with increase of the MIP sorbent make-up at a rate of 6.8 £/tCO2 per 0.1% of sorbent make-up.
Keywords: CCS; Carbon capture and storage; MEA; Monoethanolamine; MIP; Molecularly imprinted polymer